Exploring the evidence of direct threats to cetaceans from maritime vessels: A systematic map - Valeria Ferrari; Emily Hague; Marija Sciberras; Karen A. Alexander; Patrick D. O’Hara; Lauren McWhinnie (PLoS ONE, 2026)
Cetaceans face a multitude of well-recognised anthropogenic threats, many of which can be attributed to the activities of marine vessels that are increasing in number throughout the world’s oceans. This study applies a systematic map methodology to better understand the current state of knowledge on vessel impacts to cetaceans, and to identify data gaps relating to specific geographies, vessel types and species. Literature searches were undertaken in January 2023 using three databases (Scopus, Web of Science, ProQuest), yielding 28,452 results. After duplicate removal and title, abstract and full-text screening, 568 documents were included in this review, resulting in 661 records of empirical evidence being extracted for further analysis. These records highlighted a focus on certain species (bottlenose dolphins (n = 133) and humpback whales (n = 89)) and vessel types (e.g., eco-tourism boats (n = 145)), and the majority of records were from North American waters (n = 274). There was also limited evidence demonstrating impacts of vessels for entire groups of species including porpoises (n = 21) and beaked whales (n = 22). Given the global distribution of marine mammals and vessels, there were few published records available for African waters and international waters. However, for 41.4% of the records it was not possible to classify the type(s) of vessels represented. Therefore, greater clarity and recognition of the heterogeneity of vessels and their associated impacts would both help improve our understanding of potential knowledge gaps and, importantly, help refine our ability to holistically evaluate and assess the risk(s) maritime traffic poses to cetaceans.